'A necessary evil that does not "really" cure disease': The domestication of biomedicine by Dutch holistic general practitioners. (May 2016) - Raaphorst, Nadine; Houtman, Dick
Against the background of studies about the domestication of complementary and alternative medicine into biomedical settings, this article studies how biomedicine is integrated into holistic settings. Data from 19 in-depth interviews with Dutch holistic general practitioners who combine complementary and alternative medicine with conventional treatments demonstrate that they do not believe that conventional biomedicine 'really' cures patients. They feel that it merely suppresses the physical symptoms of a disease, leaving the more fundamental and non-physical causes intact. As a consequence, they use conventional biomedicine for strictly practical and instrumental reasons. This is the case in life-threatening or acute situations, understood as non-physical causes of disease having been left untreated with complementary and alternative medicine for too long. More mundane reasons for its use are the need to take patients' demands for biomedical treatment seriously or to obey authoritative rules, regulations and protocols. The integration of biomedicine into complementary and alternative medicine, then, follows the same logic of domestication of complementary and alternative medicine into biomedicine: it is made subordinate to the prevailing model of health and illness and treated as a practical add-on that does not 'really' cure people.